Comprehensive Analysis of Online Learning Effectiveness in High School in the City of Padang - Syofiani, Syofiani; Pebriyenni, Pebriyenni; Tavriyanti, Lisa (Budapest International Research and Critics University, 2021)
This research aims to comprehensively analyze the online learning effectivity at Senior High School in Padang City. The research is done by using survey method towards 16 public schools as population. The research was conducted in June 2021 by taking three subjects as samplings, such as Bahasa Indonesia (Indonesian), Bahasa Inggris (English), and PPKn (Civic Education). The questionnaire consists of 30 close-type questions using Likert scale. The amount of respondents is 2161 students of grade X and XI. The data is grouped by aspects of learning objectives, infrastructures, teachers ability using technology, time efficiency, and learning outcomes. The result shows that >70% of respondents stated that online learning can increase analytical skills and divergent thinking, and is able to develop new values. The discovery was made possible because 81% respondents stated that the device they owned is compatible for online learning. In relation to teachers ability using technology and learning models, the research resulted in >70% students stated that teachers are skilled at using technology. Also, media and learning model used by teachers are able to increase students creativity and it can achieve better learning outcomes. It can be concluded that online learning at senior high school in Padang city is effective to create conducive learning and achieve maximum learning outcomes.